Graphane Nanostripes. Issue 45 (7th September 2016) - Wang, Lu; Sofer, Zdeněk; Bouša, Daniel; Sedmidubský, David; Huber, Štěpán; Matějková, Stanislava; Michalcová, Alena; Pumera, Martin
Abstract: Graphane, the hydrogenated counterpart of graphene, was shown to exhibit properties such as tunable band gaps through varied degrees of hydrogenation, fluorescence, or ferromagnetism. Graphane nanostripe properties have also been theoretically predicted. Herein, we show that graphane nanostripes can be prepared by opening carbon nanotubes using Birch reduction in liquid ammonia utilizing potassium as a reducing agent and water as a proton donor. The prepared graphane nanostripes exhibit several exceptional properties when coupled with trace metal dopants. The interplay of metallic nanoparticles and defects lead to a spin polarization and induction of ferromagnetic moment, as well as to enhanced electrocatalytic properties in the hydrogen evolution reaction when compared to non‐hydrogenated carbon nanotubes. Abstract : Graphane shows its stripes : Graphane, the hydrogenated form of graphene, was prepared by a straightforward Birch reduction of carbon nanotubes. The reduction opens the nanotubes and exposes both the entire surface of the graphane sheet, as well as metal impurities normally contained within the nanotubes. These features change the magnetic and electrocatalytic properties of the material.